2016
DOI: 10.1016/j.tvjl.2015.10.043
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the growth rate of UK dairy heifers to improve future productivity

Abstract: Sub-optimal heifer growth is associated with higher disease rates and reduced future performance and longevity in the dairy herd. This manuscript describes a system for measuring heifer growth from birth to first calving used on commercial dairy farms in South West England, in order to gather benchmarking data to feed back to farmers. Weights (n = 8443) were collected from 20 farms. There was marked variation in individual and herd mean growth rates. Overall, calves gained no weight in the first eight days aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
27
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 28 publications
9
27
1
1
Order By: Relevance
“…Overall ADG in the first 5 weeks was 0.48 kg/day. This exceeded the 0.12 kg/day previously recorded by Bazeley et al (2015) on UK farms but was similar to growth rates of 0.35 to 0.56 kg/day reported in a review of 19 research studies (Morrison et al, 2009). These restrictions in milk supply occurred even though numerous studies have shown that calves fed more milk at a young age have higher feed conversion efficiencies and better growth rates (e.g.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Overall ADG in the first 5 weeks was 0.48 kg/day. This exceeded the 0.12 kg/day previously recorded by Bazeley et al (2015) on UK farms but was similar to growth rates of 0.35 to 0.56 kg/day reported in a review of 19 research studies (Morrison et al, 2009). These restrictions in milk supply occurred even though numerous studies have shown that calves fed more milk at a young age have higher feed conversion efficiencies and better growth rates (e.g.…”
supporting
confidence: 79%
“…This allowed for compatible comparisons between all calves, regardless of the exact age at each measurement. No adjustments were made for recruitment size because many calves either maintain a steady weight or even lose weight in their 1 st week (Bazeley et al, 2015), meaning that a linear growth rate could not be assumed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, there may be an opportunity for interventions during early post‐natal life in calves, by modulating the catch‐up growth and preventing the development of metabolic diseases in later life (Jimenez‐Chillaron et al., ). Recent studies have shown both a very limited and an enhanced diet in young calves to have potential negative consequences for their later performance (Bazeley et al., ; Brickell et al., ; Moallem et al., ; Shamay et al., ). Hence, the principal challenge is to develop an optimal growth rate, ensuring a short‐term survival and resistance against diseases, without disturbing fertility and metabolic health in later life.…”
Section: Implications For Replacement Heifer Rearing Practicesmentioning
confidence: 99%
“…Although heifer rearing has gained interest over the last years, a recent study in UK dairy heifers has shown a very poor growth pre‐weaning, with negative effects on health and welfare of the calves (Bazeley et al, ). Hence, optimization of rearing strategies is necessary.…”
Section: Introductionmentioning
confidence: 99%